AKUNTANSI POLITIK: FAKTOR POLITIK DALAM PENGELOLAAN ANGGARAN OTONOMI KHUSUS PAPUA - Muhammad Aras Prabowo; Lusiana Putri Ahmadi; Muhammad Asdar Prabowo (Jurnal Akuntansi Bisnis, 2022)
ABSTRACT : The budget for Papua's special autonomy will end in 2021, so it is important to do an in-depth study to increase budget productivity in an academic framework through scientific research. The purpose of this research is to analyze the budget management of Papua's special autonomy from the political and accounting perspective. The method used is a qualitative approach by using supporting data regarding the management of state finances, the budget cycle and the special autonomy budget of the Papua’s Province. This study attempts to explain political accounting in Papua’s Special Autonomy budget management. The research method used is a literacy study by utilizing various sources that are related to the research topic, both from scientific articles, books, journal publications and sources from official government websites and other relevant sources. The research process is carried out by collecting data, grouping data, analyzing data to describing it in the form of results and research discussions. The results showed that between politics, budget accounting and government accounting have a relationship in the management of the Papua’s special autonomy budget, then referred to by researchers as political accounting. Political accounting is a series of comprehensive processes both from the political side, the budget to the reporting system and evaluation of the realization of the use of the budget. The theoretical implication is that there is a wedge between political science through the fields of politics and budget accounting and government from the perspective of Papua's special autonomy budget. This finding adds a new treasure in multi-paradigm accounting research, namely political accounting.Keywords: Accounting, Politics, Budget Management, Papua Special Autonomy ABSTRAK : Anggaran otonomi khusus Papua akan berakhir tahun 2021, sehingga pendalaman untuk meningkatkan produktifitas anggaran menjadi penting dilakukan dalam kerangka akademis melalui penelitian ilmiah. Tujuan penelitian adalah menganalisa pengelolaan anggaran otonomi khusus Papua dari sisi politik dan akuntansi. Metode yang dipakai adalah pendekatan kualitatif dengan menggunakan data-data pendukung mengenai pengelolaan keuangan negara, siklus anggaran dan anggaran otonomi khusus Provinsi Papua. Penelitian ini berusaha menjelaskan tentang akuntansi politik dalam pengelolaan anggaran Otsus Papua. Merode penelitian yang digunakan adalah studi literasi dengan memanfaatkan berbagai sember yang memiliki kaitan dengan topik penelitian, baik dari artikel ilmiah, buku, publikasi jurnal dan sumber dari website resmi milik pemerintah serta sumber lainnya yang relevan. Proses penelitian dilakukan dengan mengumpulkan data, mengelompokkan data, menganalisas data sampai dengan mendeskriftifkan dalam bentuk hasil dan pembahasan penelitian. Hasil penelitian menunjukkan bahwa antara politik, akuntansi anggaran dan akuntansi pemerintahan memiliki keterkaitan dalam pengelolaan anggaran otonomi khusus Papua, kemudian disebut oleh peneliti sebagai akuntansi politik. Akuntansi politik adalah serangkaian proses yang komprehensif baik dari sisi politik, anggaran hingga sistem pelaporan dan evaluasi realisasi penggunaan anggaran. Implikasi secara teoritis, ditemukan irisan antara ilmu politik melaui bidang-bidang politik dengan akuntansi anggaran dan pemerintahan dari perspektif anggaran otonomi khusus Papua. Temuan ini menambah khasanah baru dalam penelitian akuntansi multiparadigma yaitu akuntansi politik.Kata Kunci: Akuntansi, Politik, Pengelolaan Anggaran, Otonomi Khusus Papua